الأبعاد الظاهرة للشخصية الاغترابية في روايات علي بدر _ دراسة سيميائية_ - أحمد, المشرف: أ. م. د. كوثر محمد; القادر, الباحثة: بينا كامل عبد (Sulaimani Journal for Humanities, 2023)
This study dealt with the expatriate personality in the novels of the Iraqi writer Ali Badr, who succeeded in making his characters and describing them accurately, as he embodied the social, class and cultural situation through his characters. The characters in Ali Badr’s novels include the crisis of a people and a nation, and they carried expatriate loads, and five of his novels were chosen to be the subjects of this study, which are (The Winter of the Family), (The Road to Tell Mutran), (Noise, Women and a Submerged Writer), (Professors of Illusion), (Player of the Clouds). In order to enter the world of expatriate personalities and reveal the signs of their apparent dimension, and to highlight the semantic dimensions of the personality represented by the physical and social dimension in them, we have relied on semiotic concepts to reveal the codes that constitute the main axis of character building, so we poured our endeavor into interrogating the expatriate characters in those novels to reveal Implicit meanings and connotations.
Keywords: Keywordspersonality; apparent dimensions of personality; alienated personality; semiotic approach